Technological achievements in the fabrication of tubular-designed protonic ceramic electrochemical cells - Maria A Gordeeva; Artem P Tarutin; Nikolai A Danilov; Dmitry A Medvedev (Materials Futures)
Protonic ceramic electrochemical cells provide an excellent basis for the advancement of high-temperature solid oxide devices, offering potential solutions to a range of challenges in the hydrogen energy and carbon capture fields. The facilitated ionic transport in proton-conducting electrolytes enables these cells to operate at temperatures 100 °C–500 °C lower than those of conventional solid oxide cells with known zirconia electrolytes. As a result, promising performances have been reported for various types of proton ceramic electrochemical cells. Nevertheless, these advancements have been demonstrated only at the laboratory scale, whereas their ZrO _2 -based counterparts have already been commercialized. This review presents an overview of the fundamental and applied aspects related to the fabrication of tubular protonic ceramic electrochemical cells and their subsequent characterization as hydrogen permeation membranes, hydrogen pumps, hydrogen sensors, fuel cells, electrolysis cells, and electrochemical reactors. A specific focus is placed on the technological aspects of the tube preparations derived from the original powder sources as well as the dimensional characteristics of the tubes, which serve as an indicator of scaling. Therefore, this review serves as a starting point for the development and scaling of protonic ceramic electrochemical cells, with the potential for large-scale production.